Киевская Русь - Жук Светлана Михайловна (История России, 2007)
Экземпляры: ф-1 (ретроконверсия) / Инвентарный номер: 46505 / Цена: 55.00 / Сис.шифр: 63.3(2)4 / Авт.знак: Ж 85 / ГРНТИ: 03 / ББК: 63.3(2)4